Uranium Extraction by a Bifunctional Amido-Phosphonic Acid: Coordination Structure and Aggregation. Issue 3 (15th April 2016) - Pecheur, Olivia; Guillaumont, Dominique; Dourdain, Sandrine; Berthon, Laurence; Turgis, Raphael; Fillaux, Clara; Arrachart, Guilhem; Testard, Fabienne
ABSTRACT: Butyl- N, N -di(2-ethylhexyl)carbamoyl-nonylphosphonate (DEHCNPB) is a new amido-phosphonic acid bifunctional ligand with a high uranium extraction efficiency from wet phosphoric acid. In the present work, the DEHCNPB coordination structure toward uranium and its aggregation properties have been fully characterized using experimental and theoretical approaches. DEHCNPB forms associated species, and its aggregation properties such as aggregation number or CAC have been determined from SAXS and SANS measurements. The preferred site for bonding of DEHCNPB toward U(VI) has been determined from IR, EXAFS, and DFT calculations.